Watershed-scale assessment of surface water-related risks from shale gas development in mountainous areas, China. (1st February 2021) - Zhang, Hong; Lu, Peili; Zhang, Daijun; Kou, Shuangwu; Bao, Kai; Li, Chenglong; Wang, Jun; Mao, Yuanyuan
Abstract: Water risks are one of the key issues dominating environmental debates on shale gas development. Water withdrawals and wastewater discharges in shale gas fields of mountainous areas are more complicated than in plain areas due to different climatic, topographical and hydrological conditions, which would impact water resources. This research identifies the surface water-related risks from shale gas development in mountainous areas as water shortage and water pollution. Conceptions of accessibility for both water supply and water pollution are proposed to describe the vulnerability of water resources and the exposure to water pollution. Based on a risk probability model, a water risk assessment method for mountainous areas is constructed from the perspectives of dangers, exposures and vulnerabilities. Finally, the assessment method is applied in Chongqing, China. The results show that, from 2010 to 2020, the water consumption of shale gas development has a little impact on regional water resources in total, but more significant impacts are seen in a few areas, including the seasonal water-deficient areas in Western Chongqing, the urban and suburban areas with high pollutant loadings in Midwest Chongqing, and other areas with high pollutant accessibility and vulnerable water environments. The surface water-related risks of the shale gas development in Chongqing are principally composed of low and relatively low levels of risks, which cover 60% of the total area of Chongqing and display a spatial difference of west > northeast > southeast areas. Based on Monte Carlo method, the results of uncertainty analyses show the model is reliable. This research provides a reference for water comprehensive risk assessment of shale gas development in mountainous areas. Graphical abstract: Image 1 Highlights: Concept of accessibility were proposed to represent the particularity of surface water-related risksin mountainous areas. A method was proposed to assess watershed-scale surface water-related risks from shale gas development in mountainous areas. The surface water-related risks from shale gas development in mountainous area were assessed.